Cushion pressure control system for an intelligent air-cushion track vehicle - Hossain, Altab; Rahman, Mohammed Ataur; Mohiuddin, A. K. M. (Springer, 2011)
This paper presents the control system of cushion pressure for the developed intelligent air-cushion track vehicle (IACTV) for operating on swamp terrain and wet fields. A novel auto-adjusting supporting system is designed for the vehicle’s intelligent air-cushion system. Focusing on minimizing the total power demand of the vehicle, an optimization model has been established, for examining the effects of vehicle parameters and load distribution on power consumption by controlling air-cushion pressure. Then optimum cushion pressure is determined based on the developed optimum pressure — sinkage relationship and the pressure in the cushion chamber is controlled by the Fuzzy controller by maintaining volume flow rate and continuously monitored by the pressure sensor attached with the cushion chamber. The ultrasonic displacement sensor is used to measure the sinkage of the vehicle. The output voltages of the ultrasonic displacement are used to operate the pull-in solenoid switch through the microcontroller which closes the circuit of the compressor motor. Distribution of vehicle load to the air-cushion system is controlled by Fuzzy Logic controller by maintaining the inside pressure of the cushion.